Advanced phase change hydrogel integrating metal-organic framework for self-powered thermal management. (January 2023) - Cheng, Piao; Tang, Zhaodi; Chen, Xiao; Xu, Jianhang; Liu, Panpan; Zhang, Xiaowei; Wang, Ge
Abstract: With increasing global installation of photovoltaic panels and more complex functionalities of smart electronic devices, a fundamental problem in photovoltaic conversion and electronic device operation is massive heat generation, which severely reduces energy utilization efficiency and service life. Herein, we proposed a self-powered thermal management strategy integrating metal-organic framework (MOF) and liquid-gas phase change hydrogel ((Poly (vinyl alcohol)/CaCl2 ·6H2 O, PVA/CH), which is much beyond traditional solid-liquid phase change materials in phase change enthalpy. Benefiting from the self-adaptive capability of MOF, MOF@PVA/CH bilayer was capable of efficiently evaporating water molecules with a rate of ∼0.90 kg m −2 h −1 at higher temperature and capturing water molecules with a rate of 0.21 g g −1 from the surrounding humid air at lower temperature for self-regeneration. Specifically, this self-adaptive passive cooling strategy tremendously boosted the thermal management efficiency of the simulative heater, and reduced the surface temperature of solar cell by 18 ℃. Our proposed approach provides a promising reference for achieving high cooling efficiency, low-energy consumption, and self-powered thermal management for thermo-related devices. Graphical Abstract: ga1 Highlights: A self-powered high-enthalpy thermal management strategy was proposed that integrated MOF and phase change hydrogel. This MOF/phase change hydrogel bilayer with significant enhanced evaporative cooling capability was applied to solar cell. The bilayer achieved self-regenerative reversible absorption-evaporation cycles in high temperature and low temperature.